Exploring the Relationships Among Extracurricular Activities, Cultural Connectedness and School Engagement Among First Nations Youth ... - Campbell, Ian Stewart (Graduate Studies, 2018)
The current study set out to identify the relationships among school engagement, structured extracurricular activities, and cultural connectedness within a sample of Indigenous youth. Eighteen First Nations youth living in Stoney Nakoda Nation completed a demographics question questionnaire (i.e., extracurricular activities, age of participant, and who the child resides with), a school engagement measure (including behavioural, emotional, and cognitive engagement), and a cultural connectedness scale. Although no significant results were found, First Nations youth are participating in structured extracurricular activities in the form of in-school sports and out of school sports. Emotional engagement and school engagement total were moderately correlated to extracurricular activity participation. Cultural connectedness was not significantly related to extracurricular activity participation or school engagement. Furthermore, cultural connectedness did not significantly moderate the relationship between school ...